Critical role of IL‐1α in IL‐1β‐induced inflammatory responses: cooperation with NF‐κBp65 in transcriptional regulation. Issue 2 (1st October 2018) - Singh, Anil K.; Fechtner, Sabrina; Chourasia, Mukesh; Sicalo, Jerry; Ahmed, Salahuddin
ABSTRACT: The IL‐1 cytokines are considered among the first family of cytokines that orchestrate acute and chronic inflammatory diseases. Both IL‐1β and IL‐1α are members of the IL‐1 family; however, their distinct roles in the inflammatory processes remain poorly understood. We explored the role of IL‐1α in IL‐1β‐activated signaling pathways causing synovial inflammation in rheumatoid arthritis (RA). Using synovial fibroblasts isolated from RA joints, we found that IL‐1β significantly stimulated IL‐1α expression, which was selectively inhibited by blocking the NF‐κB pathway. Knockdown of IL‐1α using small interfering RNA abolished IL‐1β‐induced pro‐IL‐1α and pro‐IL‐1β expression and suppressed inflammation. Native and chromatin immunoprecipitation studies showed that IL‐1α cooperates in NF‐κBp65 binding to the distal region of IL‐1α promoter and to the proximal region of IL‐1β promoter upstream of the transcription start site to stabilize their gene transcription. Molecular dynamics simulation of IL‐1α or IL‐1β binding to IL‐1 receptor showed distinct interaction sites that corroborate with the ability of IL‐1α to differentially activate phosphorylation of signaling proteins compared with IL‐1β. Our study highlights the importance of IL‐1α in mediating IL‐1β–induced inflammation in addition to maintaining its expression and providing a rationale for targeting IL‐1α to minimize the role of IL‐1β in inflammatory diseases like RA.—Singh, A. K., Fechtner, S., Chourasia, M., Sicalo, J., Ahmed, S. Critical role of IL‐1α in IL‐1β–induced inflammatory responses: cooperation with NF‐κBp65 in transcriptional regulation. FASEB J. 33, 2526–2536 (2019). www.fasebj.org